Risk Assessment, Genetic Testing and Management of Lynch Syndrome - Grover, Shilpa (2010)
Of the estimated 150,000 colorectal cancer (CRC) cases diagnosed annually, approximately 30% have a familial basis and 3–5% are due to high penetrance inherited cancer syndromes. Lynch syndrome or hereditary non polyposis colorectal cancer (HNPCC), caused by inherited germline mutations in mismatch repair (MMR) genes, is the most commonly inherited CRC syndrome. It is characterized by young onset CRC and an increased risk for extra-colonic tumors, including gynecologic, urinary tract and other gastrointestinal cancers. Commercial testing is available for mutations in the MMR genes but testing all CRCs would be economically prohibitive. Therefore a comprehensive evaluation of a multigenerational family cancer history is essential for the identification of at-risk individuals. The presence of tumors diagnosed at a young age, multiple first- and second-degree relatives with cancer or 2 or more primary cancers may be indicative of an inherited cancer syndrome and such individuals should undergo genetic evaluation. Genetic test results, when conclusive, can guide management for both patients and their families. However, indeterminate test results may provide false reassurance to patients who continue to be at higher than average risk. With on-line risk assessment tools and commercial genetic testing, there is potential to identify a greater number of at-risk individuals at an earlier age. However, for these measures to improve outcomes, patients must receive screening recommendations and counseling appropriate for their cancer risk.